IDENTIFICATION OF ASTRONOMIC MISCONCEPTIONS IN STUDENTS WITH CONFIDENCE DISCRIMINATION QUOTIENT ANALYSIS TECHNIQUES - Winny Liliawati (Jurnal Pengajaran MIPA, 2021)
This study aimed to identify the astronomical misconceptions of student-teacher candidates using the Confidence Discrimination Quotient. The research method uses Explanatory Sequential Design, with a four-tier instrument Astronomy diagnostic test and interviews. Participants are 93 students spread across six universities in Indonesia. The misconceptions identified include: temperatures during the summer are warmer than in winter because the Earth is closer to the Sun; tides caused by the phases of the Moon; The moon always rises at the same time every day. This study concludes that most students experience misconceptions related to the motion and position of celestial bodies.